Helios Observations of Quasiperiodic Density Structures in the Slow Solar Wind at 0.3, 0.4, and 0.6 AU. Issue 2 (21st February 2019) - Di Matteo, S.; Viall, N. M.; Kepko, L.; Wallace, S.; Arge, C. N.; MacNeice, P.
Abstract: Following previous investigations of quasiperiodic plasma density structures in the solar wind at 1 AU, we show using the Helios1 and Helios2 data their first identification in situ in the inner heliosphere at 0.3, 0.4, and 0.6 AU. We present five events of quasiperiodic density structures with time scales ranging from a few minutes to a couple of hours in slow solar wind streams. Where possible, we locate the solar source region of these events using photospheric field maps from the Mount Wilson Observatory as input for the Wang‐Sheeley‐Arge model. The detailed study of the plasma properties of these structures is fundamental to understanding the physical processes occurring at the origin of the release of solar wind plasma. Temperature changes associated with the density structures are consistent with these periodic structures developing in the solar atmosphere as the solar wind is formed. One event contains a flux rope, suggesting that the solar wind was formed as magnetic reconnection opened up a previously closed flux tube at the Sun. This study highlights the types of structures that Parker Solar Probe and the upcoming Solar Orbiter mission will observe, and the types of data analyses these missions will enable. The data from these spacecrafts will provide additional in situ measurements of the solar wind properties in the inner heliosphere allowing, together with the information of the other interplanetary probes, a more comprehensive study of solar wind formation. Key Points: Quasiperiodic solar wind density structures observed closer to the Sun than ever before by in situ data Concomitant density/temperature enhancements suggest the release of coronal plasma from closed‐field regions by magnetic reconnection One occurrence of quasiperiodic structures maps to a region far from the heliospheric current sheet, supporting the S‐web model of the slow solar wind